(untitled) (Vietnam Journal of Community Medicine, 2021)
A self-controlled intervention study was conducted on a group of hearing loss children who wear hearing aids at the National Children Hospital January 2018 to August 2019. The purpose of the study is to evaluate the effectiveness of the hearing aid on these children. Data were taken by questionnaires and analyzed using Stata software. The results showed that the average improvement of the hearing threshold in 71 hearing loss ears after wearing hearing aids was 49.2 ± 9.5dB. In which improvement at frequency 500 Hz is 47.5 ± 10.9dB; frequency 1000 Hz is 49.9 ± 10.5dB; frequency 2000 Hz is 50.2 ± 10.1dB; frequency 4000 Hz is 47.9 ± 10.2dB. The SII index improve 38.5 ± 27.4%. The Maximum word comprehension improve 60.9 ± 38.5%. The Maximum sentence comprehension improve 73 ± 34.2.